Association of Stress Hyperglycemia and Adverse Cardiac Events in Acute Myocardial Infarction - A Cohort Study - Rajpurohit, Annu; Sejoo, Bharat; Bhati, Rajendra; Keswani, Prakash; Sharma, Shrikant; Sharma, Deepak; Meena, Durga S.; Midha, Naresh Kumar (Cardiovascular & Haematological Disorders - Drug Targets, 2021)
Background: Stress hyperglycemia is a common phenomenon in patients presenting with acute myocardial infarction (MI). We aim to evaluate the association of stress hyperglycemia at the time of hospital presentation and adverse cardiac events in myocardial infarction during the course of hospital stay. Methods: Subjects with age ≥18 years with acute MI were recruited on hospital admission and categorized based on admission blood glucose (<180 and ≥180 mg/dl, 50 patients in each group). Both groups were compared for clinical outcomes, adverse cardiac events and mortality. We also compared the adverse cardiac outcomes based on HbA1c levels (<6% and ≥6%). Results: Patients with high blood glucose on admission (stress hyperglycemia) had significant increased incidences of severe heart failure (Killip class 3 and 4), arrythmias, cardiogenic shock and mortality (p value = 0.001, 0.004, 0.044, and 0.008 respectively). There was no significant association between adverse cardiac events and HbA1c levels (heart failure 18.8% vs. 25%, p value = 0.609 and mortality 16.7% vs. 17.3%, p value = 0.856). Conclusions: Stress hyperglycemia is significantly associated with adverse clinical outcomes in patients with MI irrespective of previous diabetic history or glycemic control. Clinicians should be vigilant for admission blood glucose while treating MI patients.
Keywords: myocardial infarction